Complex acoustic signals in Crossodactylodes (Leptodactylidae, Paratelmatobiinae): a frog genus historically regarded as voiceless. Issue 2 (4th March 2022) - Santos, Marcus Thadeu T.; Barata, Izabela M.; Ferreira, Rodrigo B.; Haddad, Célio F. B.; Gridi-Papp, Marcos; de Carvalho, Thiago R.
ABSTRACT: Vocal sounds occur in most anurans and are often emitted as simple and stereotyped acoustic signals. Some frog groups, however, have complex signals and others can produce distinctive acoustic structures, such as purely ultrasonic calls. Crossodactylodes is a genus of bromeligenous frogs that is understudied in many aspects. This genus has been historically regarded as voiceless, but recent studies reported briefly on vocal sounds in two species. Here, we provide the first quantitative description of vocalisations of Crossodactylodes frogs and describe the vocal repertoires of three species. Vocalisations are formed of up to three call types, reported herein as creaking, chirp and squeak calls. We discuss the major call patterns and the repertoire of Crossodactylodes . We also discuss the evolutionary and functional implications of the low-intensity calls produced at the water–air interface inside bromeliads. The absence of some morphological structures normally involved in sound reception (elements of the middle ear) in Crossodactylodes frogs indicates that extratympanic pathways might be the main auditory route in these highly specialised leptodactylids.